2017
DOI: 10.3390/app7070694
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Permeability Characteristics of Latex-Modified Fiber-Reinforced Roller-Compacted Rapid-Hardening-Cement Concrete for Pavement Repair

Abstract: This study evaluated the effects of reinforcement fibers on the mechanical characteristics, chloride ion penetration properties and abrasion resistance of roller-compacted latex-modified fiber-reinforced rapid-hardening-cement concrete (RCLMFRRHCC) for use in the emergency repair of concrete pavements. The reinforcement fibers tested included macro synthetic fibers (a structural fiber) as well as PVA (polyvinyl alcohol) and natural Jute fibers (non-structural fibers). In the experiment, compressive strength, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…e study was conducted to apply microsilica as a substitute material for rapid-hardening cement in order to reduce the using amount of rapid-hardening cement. e addition of microsilica brings about the pozzolanic reaction and a fine pore-filling effect, providing increased strength and improved water tightness [16,17]. Also, this study added macrosynthetic fibers and natural jute fibers which showed good results in the previous study.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…e study was conducted to apply microsilica as a substitute material for rapid-hardening cement in order to reduce the using amount of rapid-hardening cement. e addition of microsilica brings about the pozzolanic reaction and a fine pore-filling effect, providing increased strength and improved water tightness [16,17]. Also, this study added macrosynthetic fibers and natural jute fibers which showed good results in the previous study.…”
Section: Introductionmentioning
confidence: 67%
“…In the preliminary study [16], it was decided to apply about 5%, considering the range of latex that can be roller compaction methods on the type of fiber reinforcement. e reinforcement fibers, macrosynthetic fiber and jute fiber, were added at a volume ratio of 0.10%.…”
Section: Proportionsmentioning
confidence: 99%
See 3 more Smart Citations